Test pit excavation within currently occupied rural settlements in the Czech Republic, Netherlands, Poland and United Kingdom – Results of the CARE project 2021 - Lewis, Carenza; Vařeka, Pavel; van Londen, Heleen; Verspay, Johan; Marciniak, Arkadiusz; Kajda, Kornelia; Kobiałka, Dawid (Medieval Settlement Research, 2022)
In 2021 the four-nation CARE project, ‘Community Archaeology in Rural Environments Meeting Societal Challenges’ (CARE-MSoC), continued archaeological test pit excavations within currently inhabited rural settlements of known or suspected medieval date in the Czech Republic, Netherlands, Poland and the UK. As in 2020, the number of test pit excavations that could be carried out was severely restricted in 2021 by the continuing COVID-19 pandemic, but limited work was possible in seven settlements: Drválovice, Merboltice, Předhradí, Vanovice (all in the Czech Republic), Liempde (Netherlands), Biadki (Poland) and Riseholme (UK) (Fig. 1). The results of these excavations are summarised here, as an update to previous reports reviewing test pit excavations in 2019 and 2020 (Lewis et al. 2020; 2021).